Manajemen Pengadaaan Kemasan UMKM Toishii Takoyaki Menggunakan Metode Analytycal Hierarcy Process (AHP) - Leksonowati, Vera; Binawan, Muhammad Vega; Manurung, Yesyka Maria Magdalena (Study Program of Industrial Engineering, Udayana University, 2025)
Takoyaki is a famous and popular traditional Japanese dish, found in street markets and Japanese restaurants alike. High entrepreneurs make takoyaki widely sold in Indonesia. One of the UMKM that produces takoyaki is Toishii Takoyaki. Toishii Takoyaki offers several options for takoyaki menu quantities, which require different packaging. The varied packaging needs make Toishii Takoyaki business owners need to choose the most optimal supplier in terms of quality, price, distance, production time, and product completeness. The Analytical Hierarchy Process (AHP) method is one of the decision-making methods for selecting packaging suppliers in the Toishii Takoyaki UMKM problem. The results of calculations using the AHP method indicate that Alfatih Sablon is the most optimal supplier, with the most significant weight value of 0.50. The second optimal solution is an online shop, which has a weight value of 0.28, and the third optimal solution is Digi Bali with a weight value of 0.21.